Migraine in Thai children: Prevalence in junior high school students - Anannit Visudtibhan (2018)
A cross-sectional study to determine the prevalence of migraine in seventh grade Thai students in 4 junior high schools in Bangkok, Thailand, according to the diagnostic criteria of the second edition of the Classification of Headache of the International Headache Society was conducted in July 2004. The study included a screening self-administered questionnaire and face-to-face interview with physical examination. The diagnosis of migraine was made and confirmed by 2 pediatric neurologists. All of 1789 students in participating schools completed the questionnaire. After 2 interviews, 248 students (13.8%) were diagnosed with migraine. The prevalence in girls was higher than that in boys (16.2% vs 11.7%). Migraine as having aura was diagnosed in 34 students (13.7%). One student had sporadic hemiplegic migraine. Among 248 children, 176 (71%) reported the duration of headache between 1 and 2 hours. The leading precipitating factor of migraine was the stress related to daily school activities (17.7%). There were 32 students (12.9%) with frequent and intense headache who were referred to their primary physicians for further management. This study had disclosed a high prevalence of migraine in seventh grade Thai students in Bangkok City and reflected the existing burden of this illness in Thai students. © Sage Publications, Inc. 2007.